Pelatihan Deteksi Formalin dan Rhodamin B dalam Makanan bagi Guru dan Wali Murid TK Bintara Jaya Bekasi - Sofia Fatmawati; Hurip Budi Riyanti; Kori Yati (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2020)
People in general, consumes food which is homecooked or buying finished products every day. Many types of prepared fast foods used food additives such as preservatives, flavorings agents, sweeteners etc. Additives which being used must be safe for consumption in a certain limit. The community service was held to the teachers and parents from Bintara Jaya Bekasi Kindergarten in order to quickly detect additional ingredients of fformaldehyde and rhodamine in food and using a test kit. The target is to increase the knowledge and skills of the teachers and parents from Bintara Jaya Bekasi Kindergarten students to detect and test foods containing formaldehyde and rhodamine B because the commons does not yet understand between safe and prohibited food additives. This workshop can improve the quality of health in the school and family environment. The training was done by lecturing method, practicing rapid detection and using a test kit and followed by discussion. The results of the community service showed an increase in the knowledge and skills of the teachers and parents from Bintara Jaya Bekasi Kindergarten in detecting foods containing formaldehyde and rhodamine B.